2014
DOI: 10.1021/np4009046
|View full text |Cite
|
Sign up to set email alerts
|

Stilbenes as κ-Selective, Non-nitrogenous Opioid Receptor Antagonists

Abstract: The natural stilbene pawhuskin A has been shown to function as an opioid receptor antagonist, with preferential binding to the κ receptor. This finding encouraged assembly of a set of analogues to probe the importance of key structural features. Assays on these compounds determined that one (compound 29) shows potent opioid receptor binding activity and significantly improved selectivity for the κ receptor. These studies begin to illuminate the structural features of these non-nitrogenous opioid receptor antag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
55
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(56 citation statements)
references
References 54 publications
1
55
0
Order By: Relevance
“…1012 Our studies of the pawhuskins have led to the synthesis of pawhuskin A ( 1 ) 13 and C ( 2 ) 14 (Figure 1) as well as several analogues, and to the demonstration that compound 1 is a moderately selective KOP antagonist. During these explorations we synthesized compound 3 , 15 with the prenyl group on the “left-half” of the molecule (the portion biochemically derived from shikimate) placed in a different orientation than in the parent pawhuskin A. To our surprise, this regioisomer turned out to be an opioid receptor antagonist with high selectivity for the KOP (δ/κ > 67 and δ/μ > 67) and to be a bit more potent than pawhuskin A (K e = 0.15 μM vs. 0.20 μM).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1012 Our studies of the pawhuskins have led to the synthesis of pawhuskin A ( 1 ) 13 and C ( 2 ) 14 (Figure 1) as well as several analogues, and to the demonstration that compound 1 is a moderately selective KOP antagonist. During these explorations we synthesized compound 3 , 15 with the prenyl group on the “left-half” of the molecule (the portion biochemically derived from shikimate) placed in a different orientation than in the parent pawhuskin A. To our surprise, this regioisomer turned out to be an opioid receptor antagonist with high selectivity for the KOP (δ/κ > 67 and δ/μ > 67) and to be a bit more potent than pawhuskin A (K e = 0.15 μM vs. 0.20 μM).…”
mentioning
confidence: 99%
“…To our surprise, this regioisomer turned out to be an opioid receptor antagonist with high selectivity for the KOP (δ/κ > 67 and δ/μ > 67) and to be a bit more potent than pawhuskin A (K e = 0.15 μM vs. 0.20 μM). 15 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pawhuskin A has recognized to function as an opioid receptor antagonist, with special binding to the k receptor. Pawhuskin A is the most active natural compound making a small group of nonnitrogenous compounds with effect on the opiate receptor system [56].…”
Section: Pawhuskin Amentioning
confidence: 99%
“…Because of a long running interest in the synthesis and biology of prenylated stilbenes,[59, 60] we undertook the total synthesis and testing of this compound and demonstrated that it is a selective KOR antagonist. [61, 62] Subsequently, a medicinal chemistry program was established which has resulted in the synthesis of both DOR (2)[63, 64] and KOR (3)[63, 64] selective antagonists that are analogues of the natural product. These compounds are structurally unrelated to the classical opioids, and do not have the basic nitrogen found in morphine and other clinically used compounds such as meperidine, fentanyl or the antagonist naltrexone.…”
Section: Introductionmentioning
confidence: 99%